PEMBINAAN AKHLAK KELUARGA MENURUT PRESPEKTIF AL-QURAN DAN AS-SUNNAH - Suranto, Muh; Hakim, Azhari Latif Rahman (MAMBA'UL 'ULUM, 2024)
The increasingly degenerate morals of society today are a direct impact of advances in technology and information. Therefore, efforts to improve society's morals must be carried out as soon as possible. To create a good social order, of course it starts from the family. This research shows that: (1) The husband's morals towards his wife are giving a dowry, providing a living, interacting with his wife as well as possible and guiding and educating his wife's religion. (2) The wife's morals towards her husband are obeying her husband in terms of goodness, being the best wife and interacting with her husband as well as possible. (3) The morals of parents towards children are paying attention to the child's growth and development and educating the child's religion. (4) Children's morals towards their parents, namely when the parents are still alive, speak to them with good manners, courtesy and gentleness, obey and follow the parents' wishes as long as they do not disobey Allah and pray for both of them. If a parent has died, then filial piety is carried out by taking care of both of their bodies as well as possible, paying off their debts, carrying out their will, continuing the friendship that they both built when they were alive, glorifying both of their friends, praying and giving alms on behalf of both of them.